The methodology and the use of supplementary material and their influence in the learning of the english language with the students of 8th, 9th and 10th years of basic education at technological superior institute “Daniel Alvarez Burneo”. academic year 2009 - 2010 - GONZÁLEZ PALADINEZ, MÓNICA CRISTINA (2011)
The present research work titled: THE METHODOLOGY AND THE USE OF SUPPLEMENTARY MATERIAL AND THEIR INFLUENCE IN THE LEARNING OF THE ENGLISH LANGUAGE WITH THE STUDENTS OF 8th, 9th AND 10th YEARS OF BASIC EDUCATION AT TECHNOLOGICAL SUPERIOR INSTITUTE “DANIEL ALVAREZ BURNEO”. ACADEMIC YEAR 2009 – 2010, has been made with the purpose of discovering if the methodology applied by part of teachers and the supplementary material used by them contribute with the students’ learning development. In the development of this research, we made use of the scientific method as a general method that helped us to discover the main problem. As particular methods we used the descriptive one to describe the data obtained, the analytic-synthetic to analyze the results; and the explicative method to explain the phenomena and to elaborate the report. The instrument that we applied to gather the information needed was the survey to teachers and students. In order to process the information we made use of the logical analysis with descriptive statistic that helped us to represent the results in tables and graphs. One of the main conclusions that we found was the fact that the teachers do not prepare and use supplementary material to support their classes; and they are working with traditional methods, which affects the students’ learning.